A Robust WENO Type Finite Volume Solver for Steady Euler Equations on Unstructured Grids (Communications in Computational Physics, 2011)
A recent work of Li et al. [Numer. Math. Theor. Meth. Appl., 1(2008), pp.92-112] proposed a finite volume solver to solve 2D steady Euler equations. Althoughthe Venkatakrishnan limiter is used to prevent the non-physical oscillations nearby theshock region, the overshoot or undershoot phenomenon can still be observed. Moreover,the numerical accuracy is degraded by using Venkatakrishnan limiter. To fix theproblems, in this paper the WENO type reconstruction is employed to gain both theaccurate approximations in smooth region and non-oscillatory sharp profiles near theshock discontinuity. The numerical experiments will demonstrate the efficiency androbustness of the proposed numerical strategy.